Informed consent, or bioethics principles in education - M. S. Gorbuleva (Высшее образование в России)
The article addresses to the problem of a failure of adaptation in national educational practice. From the positions of bioethics and basing on the information-synergistic approachthere are discussed some reasons of a spontaneously arising of different types marginalcommunities. The methodological solution to the problem is obtained within the framework of the RFFI grant № 11-06-00160. The research results were supported by a grant RGNF №12-03-00198.